2014
DOI: 10.1590/1414-431x20143698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute administration of selective serotonin reuptake inhibitors on sympathetic nerve activity

Abstract: Serotonergic mechanisms have an important function in the central control of circulation. Here, the acute effects of three selective serotonin (5-HT) reuptake inhibitors (SSRIs) on autonomic and cardiorespiratory variables were measured in rats. Although SSRIs require 2-3 weeks to achieve their full antidepressant effects, it has been shown that they cause an immediate inhibition of 5-HT reuptake. Seventy male Wistar rats were anesthetized with urethane and instrumented to record blood pressure, heart rate, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Pretreatments of the selective SERT inhibitor fluoxetine (3 mg/kg), the NET-preferring inhibitor desipramine (3 mg/kg), the DAT-preferring inhibitor bupropion (10 mg/kg), or saline, occurred 30 minutes before administration of 10 mg/kg MDPV. The pretreatment doses used in the present study were the largest doses we tested that were within the dosing ranges used in the literature to selectively block monoamine reuptake (e.g., Eriksson et al, 2011; Fish et al, 2004; Klevin and Koek, 1998; Shen et al, 2013; Tiradentes et al, 2014; Valentini et al, 2006). Data obtained using smaller doses of the pretreatment compounds produced no effects on any of the endpoints examined (data not shown), and larger doses of the pretreatment compounds were not used in the present study because transporter selectivity would be unlikely to be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Pretreatments of the selective SERT inhibitor fluoxetine (3 mg/kg), the NET-preferring inhibitor desipramine (3 mg/kg), the DAT-preferring inhibitor bupropion (10 mg/kg), or saline, occurred 30 minutes before administration of 10 mg/kg MDPV. The pretreatment doses used in the present study were the largest doses we tested that were within the dosing ranges used in the literature to selectively block monoamine reuptake (e.g., Eriksson et al, 2011; Fish et al, 2004; Klevin and Koek, 1998; Shen et al, 2013; Tiradentes et al, 2014; Valentini et al, 2006). Data obtained using smaller doses of the pretreatment compounds produced no effects on any of the endpoints examined (data not shown), and larger doses of the pretreatment compounds were not used in the present study because transporter selectivity would be unlikely to be maintained.…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism whereby beta 1-adrenergic upregulation in ischemic-brain regions might improve recovery remains to be answered. Additionally, another study in rats demonstrated that acute peripheral administration of SSRIs induces changes in autonomic cardiovascular function mediated by inhibition of sympathetic activity, presumably via a central mechanism (Tiradentes et al 2014). However, it remains speculative whether SSRI-induced central sympathoinhibition and consecutive changes in autonomic cardiovascular function (such as increase in heart rate variability or improved vasomotor reactivity) might contribute to post stroke recovery or have beneficial effects on prevention of recurrent cardiovascular events in humans.…”
Section: Modulation Of the Autonomic Nervous Systemmentioning
confidence: 99%
“…Fluoxetine and sertraline, but not paroxetine, cause a reduction in heart rate that was nearly parallel to the sympatho-inhibition. In the same research, fluoxetine and sertraline did not increase blood pressure [19,20].…”
Section: Discussionmentioning
confidence: 76%